THIS IS LAPLAND! : The Formation of the Image of Lapland in Finnish Films - Räisänen, Riika (fi=Turun yliopisto|en=University of Turku|, 2017)
This Master’s thesis is about films made in Lapland. The thesis is an analysis about what kind of image the films mediate and how that image has evolved over the years. The main material used for the analysis are 6 films that were selected somewhat at random, but so that they represent different genres and were produced at different times; the oldest film being from the early 1950s and the most recent having come out in 2013. Thematic analysis has been used as the main method in this thesis; the main themes and the categories within the themes to be analysed were created after watching all the films first and gathering data while watching. There are all together five themes and seven categories. Within the themes and categories, resemblances and differences were looked at, in order to see if there were clear differences between genres or if conclusions could be drawn that the film making year had impact on the way themes were dealt with in the films. The previous research on how Lapland has been shown in visual arts served as a good starting point for the research and the thesis could be seen as a continuation to that research. Despite of some differences between the films and occasional lack of a theme in a film, we can conclude based on the analysis that the time has not changed much the way films depict Lapland, or the way the films deal with the themes that were central in the analysis. It is however visible that the way the films have shown and still continue to show Lapland is part of the long tradition of dealing with Lapland as a remote god-forsaken place where wolves howl on the white fells, where people are loud and magic is omnipresent. The thesis and the results of the analysis provide us with useful information about what kind of frames the films create and have created of Lapland. It makes it possible for us to evaluate how much of that image corresponds with reality. If we understanding how the image of Lapland has been formed, it is possible for us to break away from presumptions and it becomes possible for us to create our own experiences of Lapland. Analysis like the one in this thesis can and should be applied to other regions as well. If the way the films shape our ideas of other nations, regions, and people was studied more, the understanding that would follow could be very useful in breaking prejudices in today’s society.